Pengaruh Harga dan Fasilitas Terhadap Minat Berkunjung Kembali - Puteri Aisyah; Yustina Chrismardani (MES Management Journal, 2024)
This research aims to determine the effect of price and facilities on revisit intention at Lon Malang Beach, Sokobanah District, Sampang Regency. This research is quantitative research with data collection through questionnaires to measure the number of respondents' responses. Data were analyzed using a linear regression analysis. The sampling technique uses purposive sampling technique. A total of 100 respondents who had visited Lon Malang Beach were used as research samples. The results of the research show that price and facilities have a significant effect on revisit intention.